Analisis Proses Investigasi Dekstop PC Yang Terhubung Layanan Private Cloud - Irfan Febrian Editia Kurdiat; Nur Widiyasono; Husni Mubarok (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Private Cloud Computing ServicesÂ  is one of current technology advances that can meet the needs of companies and organizations, many cloud service providers to offer facilities at affordable costs. However, in addition to bringing the benefits, cloud services can be misused by insiders in the company to commit cyber crimes that hurt companies such as leakage of confidential data, take advantage of the company itself, data manipulation etc. Handling process in such cases it is necessary to use a digital forensic investigation to obtain information from the digital evidence. This research used EEDI (End to End Digital Investigation) in the process of investigation on the desktop side by getting the files and folders associated with crimes. The results of an investigation carried out in the form of information proving that the offender is committing a crime, The information then presented in the form of a forensic report which will be used during the trial.Keywordsâ€”Acquisition, Digital evidence, Digital forensic, investigation